Uptake, Barriers, and Determinants of e-Learning Among University Students in Selected Low Income Countries in Sub-Saharan Africa Amidst the COVID-19 Disruption: An Online Survey - Nyemike Simeon A; Abdulmujeeb Babatunde A; Lukman Abiodun N; Omogbadegun Olu R; Ido Emem A (Advances in Medical Education and Practice, 2022)
Awunor Nyemike Simeon,1,2 Aremu Abdulmujeeb Babatunde,1,3 Nafiu Lukman Abiodun,4 Richard Omogbadegun Olu,3 Awunor Ido Emem5 1Department of Community Medicine, Islamic University in Uganda, Kampala, Uganda; 2Department of Community Medicine, Faculty of Clinical Medicine, Delta State University, Abraka, Nigeria; 3Department of Anatomy, Islamic University in Uganda, Kampala, Uganda; 4Department of Statistics, Kabale University, Kabale, Uganda; 5Department of Computer Science and Information Technology, International University of East Africa, Kampala, UgandaCorrespondence: Aremu Abdulmujeeb Babatunde, Department of Anatomy, Islamic University in Uganda, Kampala, Uganda, Tel +256 754407054, Email abumujaeed@gmail.comBackground: The Coronavirus pandemic has affected educational systems worldwide, leading to the widespread closure of schools in the affected countries with a phased reopening over time. The objective of this study was to determine the uptake, barriers, and determinants of e-learning among university students in Uganda and Nigeria following the COVID-19 disruption in 2020.Methodology: A total of 240 respondents comprising University students participated in this survey. It was a cross-sectional descriptive study using a self-administered structured online questionnaire using Google documents. Data were analyzed using IBM SPSS v.21 with statistical significance set at p< 0.05.Results: The modal age group was 21– 25 years at 128 (53.3%) participants, uptake of e-learning was 159 (66.3%). The majority of respondents used a smartphone (98.8%) for the internet, with WhatsApp platform (63.7%) as the most frequently used for e-learning. Barriers to e-learning, as self-reported by respondents, were the cost of internet services (82.1%), internet inaccessibility (68.8%), lack of institutional support (47.1%), and lack of training (40.8%). Determinants of e-learning were age (p< 0.001) and sex (p=0.026).Conclusion: Two thirds of the university students had ever been taught online before the lockdown. Barriers to e-learning were mainly the cost of internet services and internet inaccessibility. Age and sex of respondents were determinants of e-learning use among University students. It is recommended that students be trained and facilitated by the Universities to adopt e-learning effectively. Governments in sub-Saharan Africa and the relevant sectors in the economy should improve the ICT infrastructure, internet accessibility, and facilitate reduction in the cost of services.Keywords: e-learning, university students, uptake, barriers, determinants, sub-Saharan Africa